2012
DOI: 10.1007/s10865-012-9471-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parent–child relationships that support physical activity in Mexican–American families

Abstract: Family-based physical activity (PA) interventions would benefit from research that identifies how to build support for PA among family members. This study examined the extent to which relationships of encouragement to do PA, and co-engagement in PA, exist among Mexican–American parents and children, and sought to identify individual, relational, and household factors associated with these dimensions of support. Participants were 224 Mexican-origin adults, with at least one child aged 5–20 years, participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…In a study of parent support for child weight loss, Epstein et al found that parents lost more weight when they were actively engaged in their child's weight loss efforts . More recently, reciprocal parent–child encouragement was found to increase co‐participation in physical activity among Mexican American families . Our data indicate that child support may be an important strategy in parental weight loss.…”
Section: Discussionsupporting
confidence: 52%
“…In a study of parent support for child weight loss, Epstein et al found that parents lost more weight when they were actively engaged in their child's weight loss efforts . More recently, reciprocal parent–child encouragement was found to increase co‐participation in physical activity among Mexican American families . Our data indicate that child support may be an important strategy in parental weight loss.…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, the child's perceptions of parental encouragement had important indirect effects in children's self-efficacy, social self-efficacy, intrinsic motivation, and self-regulation. The present findings are consistent with reports of positive associations between parents' encouragement and children's motivation in sport (e.g., Power & Woolger, 1994;Haye, Heer, Wilkinson, & Koehly, 2014;Woolger & Power, 2000).…”
Section: Mediational Effects Of the Athlete's Perceptions Of Parent'ssupporting
confidence: 92%
“…18 In contrast, family conflict, such as arguments and physical violence in the home 19 has been associated with increased substance use and deviant behavior. 20 However, few studies to date 6,21 have examined the relationships of physical activity with family cohesion and family conflict, particularly among Latino families, among whom the influence of family cohesion and family conflict on behavior may be particularly strong 22 and essential to understanding adolescent behavior.…”
mentioning
confidence: 99%